Evaluation of glucose and lipid lowering activity of arganimide a in normal and streptozotocin-induced diabetic rats - Eddouks, Mohamed; Khallouki, Farid; Owen, Robert; Hebi, Morad; Burcelin, Remy (Endocrine, metabolic & immune disorders, drug targets, 2019)
Aims: Arganimide A (4,4-dihydroxy-3,3-immo-di-benzoic acid) is a compound belonging to a family of aminophenolics found in fruit of Aigunia spinosa. The purpose of this study was to investigate the glucose and lipid lowering activity of Arganimide A (ARG A). Methods: The effect of a single dose and daily oral administration of Arganimide A (ARG A) on blood glucose levels and plasma lipid profile was tested in normal and streptozotocin (STZ) diabetic rats at a dose of 2 melte body weight. Results: Single oral administration of ARG A reduced blood glucose levels from 26.50+/-10.61 mmol/L to 14.27+/-10.73 mmol/L (p<0.0001) six hours after administration in STZ diabetic rats. Furthermore, blood glucose levels were decreased from 5.35+/-10.30 mmoLL to 3.57+/-10.17 mmol/L (p<0.0001) and from 26.50+/-0.61 mmol/L to 3.67+/-0.29 mmol/L (p<0.0001) in normal and STZ diabetic rats, respectively, after seven days of treatment. Moreover, no significant changes in body weight in normal and STZ rats were shown. According to the lipid profile, the plasma triglycerides levels were decreased significantly in diabetic rats after seven days of ARG treatment (p<0.05). Moreover, seven days of ARG A treatment decreased significantly the plasma cholesterol concentrations (p<0.001). Conclusion: ARG A possesses glucose and lipid-lowering activity in diabetic rats and this natural compound may be beneficial in the treatment of diabetes.
Gesehen am 20.11.2019